Pengaruh Ramipril terhadap Gambaran Mikroskopis Sel Neuron Otak Tikus Wistar yang Mengalami Edema Otak - Muhammad Arief Ansyar; Nita Afriani; Aisyah Ellyanti (Jurnal Ilmu Kesehatan Indonesia, 2022)
Background. Brain edema is swelling in the brain due to excessive accumulation of fluid in the brain. This condition is triggered by a decrease in cerebral blood flow (CBF) due to heart damage or isoproterenol administraion. A decrease in CBF results in brain edema which triggers damage to neuron cells. This study uses isoproterenol to induce brain edema. This damage is prevented by giving ramipril with the aim of improving cardiac and brain perfusion. Objective. To see the effect of giving ramipril to the microscopic assessment of mouses brain neuron cells with brain edema which was induced by isoproterenol. Methods. This research is an experimental study which was used 21 experimental animals which were divided into 3 groups (K-, K +, and P). The treatment group (P) was given ramipril at a dose of 3 mg/KgBW for 7 days. On the 8th and 9th day K+ and P groups were injected by isoproterenol 85 mg/KgBW to induce brain edema through AMI. Data analysis was performed using the Kruskal-Wallis Test and Mann Whitney U Test (MWUT). Results. The average number of neuron cell damage in the K -, K +, and P group, respectively, 6.2, 26.3 and 17.33. Significant differences were obtained for each group with a value of p = 0.001 (p <0.05). Conclusion. There is a significant effect of giving ramipril to the microscopic assessment of mouses brain neuron cells with brain edema which was induced by isoproterenol.